1970
DOI: 10.3329/fmcj.v6i1.7408
|View full text |Cite
|
Sign up to set email alerts
|

Disease Pattern and Health Seeking Behavior in Rural Bangladesh

Abstract: Knowledge about the existing disease pattern and health seeking behavior is essential to provide need based health care delivery to any population and to make the health care system more pro-poor. A community based cross sectional study was conducted among 493 systematically selected households in the Modhukhali Upazilla of Faridpur District to determine the prevailing disease pattern and health seeking behavior in rural Bangladesh. Data were collected through face-to-face interview of the selected respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…In a study [18] from Bangladesh, there was no major variation in the utilization of various sources of health care across different age groups in rural area, which was similar to the fi ndings of other studies. [21,22] Among the rural people, the dependence of the poorer ones is more on the quacks and better-off people rely more on the qualifi ed private practitioners, which was consistent with other studies.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In a study [18] from Bangladesh, there was no major variation in the utilization of various sources of health care across different age groups in rural area, which was similar to the fi ndings of other studies. [21,22] Among the rural people, the dependence of the poorer ones is more on the quacks and better-off people rely more on the qualifi ed private practitioners, which was consistent with other studies.…”
supporting
confidence: 83%
“…The attitude of the health provider and patient satisfaction with the treatment play a role in health-seeking behavior. [17] In a study [18] from Bangladesh, although fever was the most reported illness, only 42.3% took service from qualifi ed medical personnel or health facility and the highest percentage of patients went to quacks for the treatment of fever, whereas 11.8% sought no treatment at all. For treatment of gastrointestinal diseases, a higher portion of respondents took services from qualifi ed allopathic doctors (58.1%), although 8.1% went for self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, such factors as household monthly income per capita and working hours per day also affect the medical visitation rate of the migrant workers in Beijing. Rahman and et al (2011) Knowledge about the existing disease pattern and health seeking behaviour is essential to provide need based health care delivery to any population and to make the health care system more pro-poor. Their study concluded that it is important to develop a need based health care delivery system and actions should be taken to improve the overall scenario of health system of rural Bangladesh.…”
Section: Review Of Earlier Studiesmentioning
confidence: 99%
“…In addition, private clinics are often unaccountable to government standards of service rates and health risks. Though there is little formal data on the differences in private versus public care, one example occurs in rural Bangladesh, where traditional faith healers, homeopaths, untrained pharmacists and allopaths fill the gap in need-based healthcare delivery systems for the rural poor (Rahman et al, 2011). Similarly, among the urban poor, unregulated selling of over-the-counter pharmaceuticals and care-seeking from informal and low-quality unlicensed private clinics exacerbate the already poor health of slum-dwellers (Afsana & Wahid, 2013).…”
Section: Stemming the Medical Brain Drain: A Personal Perspective On mentioning
confidence: 99%